Innate Phagocyte Polarization in the Oral Cavity - Metcalfe, Sarah; Anselmi, Natalie; Escobar, Alejandro; Visser, Michelle B.; Kay, Jason G. (Frontiers in Immunology, 2022)
The oral cavity is a complex environment constantly exposed to antigens from food and the oral microbiota. Innate immune cells play an essential role in maintaining health and homeostasis in the oral environment. However, these cells also play a significant role in disease progression. This review will focus on two innate phagocytes in the oral cavity: macrophages and neutrophils, and examine their roles during homeostasis and disease development, with a focus on periodontal disease and cancer. Macrophages have a well-known ability to polarize and be activated towards a variety of phenotypes. Several studies have found that macrophages' polarization changes can play an essential role in maintaining health in the oral cavity and contribute to disease. Recent data also finds that neutrophils display phenotypic heterogeneity in the oral cavity. In both cases, we focus on what is known about how these cellular changes alter these immune cells' interactions with the oral microbiota, including how such changes can lead to worsening, rather than improving, disease states.